Effects of Royal Jelly Sports Gel on Exercise-Induced Muscle Damage: Evidence from Creatine Kinase and MDA (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Exercise-induced muscle damage (EIMD) commonly occurs after high-intensity resistance training, marked by elevated creatine kinase (CK) and malondialdehyde (MDA) levels, which reflect muscle damage and oxidative stress. Nutritional interventions such as royal jelly, known for its antioxidant and anti-inflammatory properties, may aid in post-exercise recovery. However, limited evidence exists regarding its effectiveness in sports gel form following intense resistance training. This study aimed to evaluate the effects of royal jelly-based sports gel on CK and MDA levels after high-intensity resistance exercise. This pilot randomized, single-blind crossover study included ten healthy male participants. Participants performed high-intensity squats and leg presses (80-90% of maximal capacity) in four sets with one-minute rest intervals. Baseline CK and MDA levels were measured 24 hours before consumption of either royal jelly-based sports gel or placebo. Post-intervention measurements were taken 24 hours later, followed by a washout period and crossover to the alternate treatment. The results revealed that royal jelly significantly reduced CK and MDA levels compared to placebo. At 96 hours post-exercise, CK decreased by approximately 10.3% in the royal jelly condition compared with 3.4% in placebo, while MDA decreased by 24.2% versus 6.2%, respectively. These findings provide preliminary evidence that royal jelly-based sports gel may contribute to improved recovery following high-intensity resistance exercise. However, results should be interpreted cautiously due to the small sample size.